Evaluating the informativeness of deep learning annotations for human complex diseases - Kushal K. Dey (Nature Portfolio, 2020)
Deep learning models have shown great promise in predicting regulatory effects from DNA sequence. Here the authors evaluate sequence-based epigenomic deep learning models and conclude that these models are not yet ready to inform our knowledge of human disease.